The Impact of Service Quality and Trust on Umrah Pilgrim Satisfaction at PT. Adhiya Tour & Travel Bandung in 2024 - fadilah, aldi fadilah; Solahudin, Dindin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
This study aims to analyze the influence of service quality and trust on the satisfaction of umrah pilgrims at PT. Adhiya Tour and Travel Bandung. Data were collected through questionnaires from a population of 132 and a sample of 30. The data analysis method used is descriptive quantitative. The results show that, partially, service quality has an influence but is not significant on the satisfaction of umrah pilgrims (t calculated 1.462 < t table 2.408; significance 0.156). On the other hand, trust has a significant influence (t calculated 5.083 > t table 2.408; significance 0.000). Simultaneously, service quality and trust significantly influence the satisfaction of umrah pilgrims (F calculated 82.304 > F table 4.21) with a determination coefficient of 86.4%, while the remaining 13.6% is influenced by other variables. Keywords : Impact of Quality; Trust; Pilgrims' Satisfaction